Shift Work and Metabolic Syndrome: Systematic Review - Silviani J Prissa; Sandra Fikawati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Compared to standard working hours, shift work is one of the most popular options. The disruption of circadian rhythms caused by shift work and the loss of circadian rhythms caused by sleep disturbances are considered to be major risk factors for the development of metabolic diseases. Objective: This systematic review analyzed the relationship of shift work to the risk of metabolic syndrome Method: Systematic searches using pubmed, scopus, proquest, science direct and google scholar were published within 2014 - 2024 using English and Indonesian. Reviews are displayed in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 and article quality assessment using the PICO framework (Patient/Population, Intervention, Comparator/Control, and Outcome). Result: 9 out of 10 articles show that shift workers have a higher incidence of metabolic syndrome and most studies show the effect of shift work on several indicators of metabolic syndrome. Conclusion: There is an association between shift work (night work or rotating shifts) and various metabolic syndrome disorders. Circadian misalignment due to night work activities can cause systemic metabolic dysfunction